New Bioprocessing Strategies: Development and Manufacturing of Recombinant Antibodies and Proteins - Kiss, Bob.; Gottschalk, Uwe.; Pohlscheidt, Michael; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book review series presents current trends in modern biotechnology. The aim is to cover all aspects of this interdisciplinary technology where knowledge, methods and expertise are required from chemistry, biochemistry, microbiology, genetics, chemical engineering and computer science. Volumes are organized topically and provide a comprehensive discussion of developments in the respective field over the past 3-5 years. The series also discusses new discoveries and applications. Special volumes are dedicated to selected topics which focus on new biotechnological products and new processes for their synthesis and purification. In general, special volumes are edited by well-known guest editors. The series editor and publisher will however always be pleased to receive suggestions and supplementary information. Manuscripts are accepted in English.
Market and Capacity evolvement of the Biopharmaceutical Industry -- New Mammalian Expression Systems -- Innovation in seed train cultivation and production culture -- Manufacturing of Proteins and Antibodies / Risk mitigation for the contamination by adventitious agents -- Harvest operations -- Downstream Processing Technologies / Capturing and Final Purifaction -- Fully disposable manufacturing concepts for clinical and commercial manufacturing and Ballroom Concepts -- Augmented Reality - PAT and Artificial Intelligence for innovative process monitoring and controls -- Trends and innovations in formulations, fill and finish technologies and drug delivery -- Process Integration towards continuous manufacturing -- Future direction of Manufacturing of novel molecular format - a research perspective (bispecific antibodies, ADC, Ab fragments, fusion proteins, etc -- Cell therapy manufacturing for modern therapeutics -- Gene therapy -- Modern technologies and strategies for vaccine manufacturing -- Product and Technology Lifecycle Management in the Pharmaceutical Industry -- Integrated High Throughput Development -- A different perspective - How much innovation is really needed for production of mAb by mammalian cell technology?
Keywords: Biotechnology; Pharmaceutical chemistry; Medicinal chemistry; Biotechnology; Pharmaceutics; Medicinal Chemistry